Unveiling area estimation through Newton's Forward Divided Difference Method - Harun, Nurzalina; Sadikin, Zubaidah; Che Sulaiman, Che Nurul Hanna; Basri, Nur Hamiza; Salim Nasir, Mohd Agos; Rathi, Sidik (Academica Press Solutions, 2024)
In this era of globalization and technological advancements, Malaysia stands out as a vibrant hub for innovations and technology, along with an entrepreneurial spirit. However, it appears that there will be occasions when the creation of software demands resources such as money, time, and workforce to provide quality to the user, but it is unlikely to be able to reach the ideal evolution. In this research study, a potentially novel technological interface named AppleMath will use a mathematical method called Newton's Forward Divided Difference Interpolation as a framework for area estimations. Nonetheless, there have been a few difficulties in developing this operating system: The technological industry is always evolving and there are numerous enhancements available to keep up with the newest software developments. It is difficult to monitor safety breaches to secure all user’s information. This is due to different malicious programs and viruses growing increasingly damaging, leaving it incredibly difficult for designers to find vulnerabilities in the application's safety breaches. Requests from users of this prospective software are constantly shifting, making it difficult to keep track of their personal preferences. Fortunately, there are answers to these problems: The program designer must stay up to date with the latest developments in the current programming advances. Additionally, creators of software must keep current with the most recent security patches to guarantee all users' information has been safeguarded. Software engineers must continually study evolving technological difficulties since needs change swiftly over time. The invention of this virtual interface has significance for the community since it provides practical applications for individuals amongst learners, particularly in the architectural and building professions, allowing them to explore while performing effectively in everyday situations. AppleMath can give a prominent platform for the public to use for educative reasons, hence achieving commercialization interest eventually.